On finite posets of injinj-finite type and their Tits forms - Bondarenko, V.M.; Styopochkina, M.V. (Algebra and Discrete Mathematics, 2006)
We prove one theorem on connection between
inj-finiteness of a finite poset and positive definiteness of its Tits
form.